Navigating Transparent Pork Production: Analyzing Visual Attention of The Maschhoffs Website - Nellie Hill; Maggie Elliot; Courtney Meyers (Journal of Applied Communications, 2021)
When it comes to food, consumers are increasingly concerned with the welfare of the livestock used to produce it. To display transparency and build trust with patrons, businesses such as The Maschhoffs, a pork production company, have created online tools to answer questions about production processes. This study implemented eye tracking and survey methodologies to attain insight regarding the visual attention of website visitors. While results revealed no discernable pattern of navigation among respondents, the findings illustrated a sector of the pork industry consumers expressed interest in was the breed-to-wean section of the farm. Researchers encourage agricultural communicators to develop messaging surrounding this specific process to continue building trust with consumer audiences as well as make recommendations for utilizing eye tracking to assess visual attention to websites.
Keywords: eye tracking; trust; transparency; interactive website; visual attention